Physicochemical, colorimetric properties and yield of bresaola from beef, Baladi-goat and Awassi-sheep in Lebanon - Abi-Salloum, Bachir; Al-Nahum, Maguy; Rached, Mohammed; Dimassi, Ossama (International Journal of Environment, Agriculture and Biotechnology, 2023)
Yield, physicochemical and colorimetric characteristics of bresaola from Lebanese Baladi-goat and Awassi-sheep compared to that from beef is studied. For this purpose, defatted lean meat cuts from Beef, Baladi-goat and Awassi-sheep were collected, weighed and processed following the EU-approved guidelines for Bresaola della Valtellina. The bresaola from beef (BFB) had the significantly lowest moisture and fat content compared to Bresaola from Baladi-goat (BFG), with the values of Bresaola from Awassi-sheep (BFS) being significantly the highest. Furthermore, the protein and ash content of BFB was significantly the highest, followed by the values of BFG with content of BFS being the lowest. The pH value of BFB was significantly the lowest, while there was no difference between those of BFG and BFS. There was no significant difference in the water activities of BFB, BFG and BFS (0.848±0.002). As for the colorimetric characteristics, the ΔE value of BFB with BFG is 14.74±4.10, while that of BFB with BFS is 17.88±4.10, and that of BFG with BFS is 16.00±4.10 noting that the values did not differ significantly. The BFB and BFG Hue values did not differ significantly both being significantly larger than that of BFS. The BFB and BFG Chroma values were not significantly different while both being significantly different from that of BFS. Bresaola from raw meat (kg-Bresaola/kg-raw meat) value for beef was found to be significantly higher than that of goat, with value for sheep being significantly the highest. Consequently, the opposite was true for weight loss (%).